2022
DOI: 10.1021/jacs.2c01143
|View full text |Cite
|
Sign up to set email alerts
|

Water-Assisted Proton Transfer in the Sequential Hydration of Benzonitrile Radical Cation C6H5CN•+(H2O)n: Transition to Hydrated Distonic Cation C6H4CNH+(H2O)n with n ≥ 4

Abstract: The stepwise hydration of the benzonitrile•+ radical cation with one–seven H2O molecules was investigated experimentally and computationally with density functional theory in C6H5CN•+(H2O) n clusters. The stepwise binding energies (ΔH n–1,n °) were determined by equilibrium measurements for C6H5CN•+(H2O) and for •C6H4CNH+(H2O) n with n = 5, 6, and 7 to be 8.8 and 11.3, 11.0, and 10.0 kcal/mol, respectively. The populations of n = 2 and 3 of the C6H5CN•+(H2O) n clusters were observed only in trace abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Generally, in such situations, trace H 2 O can play two roles: it can donate and accept protons, facilitating proton transfer [71][72][73] and it can form hydrogen bonds with reactants in a cocatalytic reaction. 74,75 Here, the two models were separately tested by carrying out DFT calculations, and the results showed that the trace H 2 O co-catalyzed the reaction with the acid.…”
Section: Of Esi †mentioning
confidence: 99%
“…Generally, in such situations, trace H 2 O can play two roles: it can donate and accept protons, facilitating proton transfer [71][72][73] and it can form hydrogen bonds with reactants in a cocatalytic reaction. 74,75 Here, the two models were separately tested by carrying out DFT calculations, and the results showed that the trace H 2 O co-catalyzed the reaction with the acid.…”
Section: Of Esi †mentioning
confidence: 99%